Marketing an introduction - Fisher, Victoria; Video Education Australasia (Australia : Video Education Australasia, 1995)
Using examples from the high profile computer games industry, this program provides viewers with an introduction to the principles and practices of marketing
Title from title screen
Executive producer, Neil Barrett ; camera, Rocco Fasano, Rob Murphy ; editor/graphics, Stephen Maggs
DVD format
Keywords: Marketing